Immediate Impact of Prosthetic Graft Replacement of the Ascending Aorta on Circumferential Strain in the Descending Aorta. (October 2019) - Rong, Lisa Q.; Palumbo, Maria C.; Rahouma, Mohamed; Meineri, Massimiliano; Arguelles, Gabriel R.; Kim, Jiwon; Lau, Christopher; Devereux, Richard B.; Pryor, Kane O.; Girardi, Leonard N.; Redaelli, Alberto; Gaudino, Mario F.L.; et al.
Abstract : Objectives: Prosthetic replacement of the ascending aorta (AA) can potentially modify energy propagation to the distal aorta and contribute to adverse aortic remodelling. This preliminary study employed intra-operative transoesophageal echocardiography (TOE) to assess the immediate impact of prosthetic graft replacement of the AA on circumferential strain in the descending aorta. Methods: Intra-operative TOEs in patients undergoing AA graft replacement were analysed for circumferential strain, fractional area change (FAC), dimensions (end diastolic area [EDA], and end systolic area [ESA]) in the descending aorta immediately before and after graft replacement. Deformation was assessed via global peak circumferential aortic strain (CAS), together with pulse pressure corrected strain, time to peak strain (TTP), and aortic distensibility. Results: Forty-five patients undergoing AA replacement with prosthetic graft (91% elective) were studied. Following grafting, descending thoracic aortic circumferential strain increased (6.3 ± 2.8% vs . 8.9 ± 3.4%, p = .001) paralleling distensibility (5.7 [3.7–8.6] 10 −3 mmHg vs . 8.5 [6.4–12.4] 10 −3 mmHg, p < .001). Despite slight increments in post graft left ventricular ejection fraction (LVEF) (52.3 ± 10.8% vs. 55.0 ± 11.9, p < .001), stroke volume was similar ( p = .41), and magnitude of increased strain did not correlate with change in stroke volume ( r = −.03, p = .86), LVEF ( r = .18, p = .28), or pulse pressure ( r = .28, p = .06). Descending aortic size (EDA 4 [2.7–4.6] cm 2 vs. 3.7 [2.5–5] cm 2, p = .89; ESA 4.3 [3.2–5.3] cm 2 vs. 4.5 [3.3–5.8] cm 2, p = .14) was similar pre- and post graft. In subgroup analysis, patients with cystic medial necrosis had a significantly higher post procedure CAS than patients with atherosclerotic aneurysms (9.7 ± 3.5% vs . 7.0 ± 2.3%, p = .03). Conclusions: Prosthetic graft replacement of the AA increases immediate aortic circumferential strain of the descending aorta, particularly in patients with cystic medial necrosis. Our findings suggest that grafts augment energy transfer to the distal aorta, a potential mechanism for progressive distal aortic dilation and/or dissection.